2012
DOI: 10.29044/v3i1p3
|View full text |Cite
|
Sign up to set email alerts
|

TA Treatment of Depression: A Hermeneutic Single-Case Efficacy Design Study - 'Peter'

Abstract: Hermeneutic Single-Case Efficacy Design (HSCED) is a systematic case study research method involving the cross-examination of mixed method data to generate both plausible arguments that the client changed due to therapy and alternative explanations. The present study uses HSCED to investigate the outcome of short-term TA psychotherapy with a young man with severe depression. The objective of the research was to investigate the effectiveness of short-term TA therapy for the treatment of depression and to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 21 publications
3
57
1
Order By: Relevance
“…This present study once again found TA psychotherapy to be an effective treatment for depression and supports the previous TA research by Fetsch & Sprinkle (1982), van Rijn et al (2011) and Widdowson (2012a;2012b) and significantly adds to the TA evidence base by providing a third positive outcome systematic case study, thus enabling TA to be considered for recognition as possibly efficacious for the treatment of depression (Chambless & Hollon, 1998). …”
Section: Resultssupporting
confidence: 73%
“…This present study once again found TA psychotherapy to be an effective treatment for depression and supports the previous TA research by Fetsch & Sprinkle (1982), van Rijn et al (2011) and Widdowson (2012a;2012b) and significantly adds to the TA evidence base by providing a third positive outcome systematic case study, thus enabling TA to be considered for recognition as possibly efficacious for the treatment of depression (Chambless & Hollon, 1998). …”
Section: Resultssupporting
confidence: 73%
“…This present study once again found TA psychotherapy to be an effective treatment for depression and supports the previous TA research by Fetsch & Sprinkle (1982), van Rijn et al (2011) and Widdowson (2012a;2012b) and significantly adds to the TA evidence base by providing a third positive outcome systematic case study, thus enabling TA to be considered for recognition as possibly efficacious for the treatment of depression (Chambless & Hollon, 1998). …”
Section: Resultssupporting
confidence: 76%
“…This article is the second of a series of three and represents an Italian systematic replication of previous UK-based findings (Widdowson 2012a(Widdowson , 2012b(Widdowson , 2012c(Widdowson , 2013 investigating the effectiveness of transactional analysis (TA) treatment of depression. This case was run under the auspices of the project 'Toward a transactional analysis psychotherapy recognised as empirically supported treatment: an Italian replication series design', funded by the European Association of Transactional Analysis (EATA).…”
Section: Introductionmentioning
confidence: 99%
“…Systematic case study research has already been applied to investigate TA effectiveness with people with long term health conditions (McLeod, 2013a;2013b) and HSCED methodology have been already successfully applied to TA and widely described in this Journal by Widdowson (2012a). Recently, several HSCEDs supporting TA treatment for depression (Widdowson, 2012a(Widdowson, , 2012b(Widdowson, , 2012c(Widdowson, , 2013 have been published, as was an additional adjudicated study which demonstrated effectiveness of TA for mixed depression and anxiety (Widdowson, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation